2001
DOI: 10.1183/09031936.01.99086101
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive pressure preset ventilation for the treatment of Cheyne-Stokes respiration during sleep

Abstract: Cheyne-Stokes respiration (CSR) during sleep is common in patients with congestive heart failure (CHF). This pattern of breathing fragments sleep, leading to daytime symptoms of sleepiness and fatigue. It was hypothesized that by controlling CSR with noninvasive pressure preset ventilation (NPPV), there would be a decrease in sleep fragmentation and an improvement in sleep quality.Nine patients (eight males, one female; mean±sd 65±11 yrs) with symptomatic CSR diagnosed on overnight polysomnography (apnoea/hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 39 publications
0
25
0
1
Order By: Relevance
“…19 In another study, Willson et al investigated the efficacy of bi-level PAP using 2 different types of bilevel pressure preset device. 23 However, in their study, they only demonstrated an improvement of apnea and sleep status and did not show an improvement of cardiac function. Therefore, this is the first report that has documented a statistically significant improvement in cardiac function with the use of bi-level PAP in CHF patients with CSR-CSA, despite the fact that only a small number of patients were involved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 In another study, Willson et al investigated the efficacy of bi-level PAP using 2 different types of bilevel pressure preset device. 23 However, in their study, they only demonstrated an improvement of apnea and sleep status and did not show an improvement of cardiac function. Therefore, this is the first report that has documented a statistically significant improvement in cardiac function with the use of bi-level PAP in CHF patients with CSR-CSA, despite the fact that only a small number of patients were involved.…”
Section: Discussionmentioning
confidence: 99%
“…22 Several reports have shown the efficacy of bi-level PAP for treating abnormal breathing in patients with CSR-CSA and chronic heart failure. 23,24 However, little is known about the efficacy of bi-level PAP for treating the underlying chronic heart failure. Therefore, we evaluated the efficacy of appropriate bi-level PAP therapy on cardiac function in chronic CHF patients with CSR-CSA.…”
mentioning
confidence: 99%
“…[23][24][25]29,30 The outcomes of therapy have also varied considerably, with limited evidence to establish the effectiveness of any therapy for CSA. [26][27][28][29]31,32 The majority of published literature has focused on the treatment of CSA secondary to congestive heart failure (CHF), [2][3][4][5][6][7][8][9][10][11][15][16][17][18][19][20][21][22][26][27][28][29] with very little data on patients with "primary" CSA 23,24 or CSA secondary to causes other than CHF. 33 In addition, there is very little data on the treatment of CSA related to opioid use and CSA that is concomitant with OSA.…”
Section: S C I E N T I F I C I N V E S T I G a T I O N Smentioning
confidence: 99%
“…1 Variable etiologies of CSA and the presence of concomitant disorders infl uence the choice of therapy. Thus, therapeutic options have varied markedly from positive airway pressure (PAP) devices, including continuous positive airway pressure (CPAP), [2][3][4][5][6] bilevel positive airway pressure therapy (BPAP), [7][8][9] and adaptive servoventilation, [10][11][12][13]20 to supplemental O 2 , 14-17 carbon dioxide, 21,22 and/or pharmacologic agents. [23][24][25]29,30 The outcomes of therapy have also varied considerably, with limited evidence to establish the effectiveness of any therapy for CSA.…”
mentioning
confidence: 99%
“…In a case series of nine patients with symptomatic CSR, diagnosed on overnight polysomnography [42], noninvasive pressure preset ventilation almost completely abolished CSR in all patients with a reduction in AHI from 49¡10 to 6¡5 events?h -1 (p,0.001). Arousal index was markedly decreased from 42¡6 to 17¡7 events?h -1 (p ,0.001) and sleep quality showed a trend towards improvement.…”
Section: Bi-level Pressure Support Ventilation Versus Cpap In Patientmentioning
confidence: 99%